A Longitudinal Analysis of Entries Into and Exits from the Canada’s Guaranteed Income Supplement Regime Among Seniors - Finnie, Ross; Gray, David; Zhang, Yan (Université d'Ottawa | University of Ottawa, 2015)
We focus on one particular pillar of the public retirement income network in Canada, namely receipt outcomes of the Guaranteed Income Supplement (GIS) regime. This empirical analysis is carried out in a dynamic framework. We address the extent to which individuals enter the state of GIS receipt at various ages as well as the extent to which individuals who receive GIS benefits at the earliest age of eligibility subsequently exit the regime. We first measure these transition rates, and then we focus our analysis primarily on the impact of the following three attributes of recipients: changes in marital status, entry cohort, and current age. The econometric equations include both simple transition models of both entries and exits, as well as hazard models of the probability of exiting the GIS regime. Among our many empirical findings is a non-trivial incidence of delayed entry into the regime as well as exit from the regime conditional on prior receipt of benefits. Women who transit from married to single status are more likely to enter, but the opposite finding is discerned for men. The hazard model for the risk of exiting the GIS regime conditioned on the duration of the on-going spell of receipt reveals a sharp pattern of negative duration dependence. The probability of entering the regime, conditioned on the event of not having received the benefit when one is initially eligible, becomes less and less likely as individuals age./Dans cette étude, nous portons notre attention sur un pilier du réseau de prestations de retraite publiques au Canada, le régime de supplément de revenu garanti (SRG). L’analyse empirique est effectuée dans un cadre dynamique. La question qui nous intéresse est de savoir à quel âge les individus entrent dans le régime et si ceux qui reçoivent le SRG dès l’âge minimal d’admissibilité quittent le régime par la suite. Nous mesurons ces taux de transition et nous nous penchons ensuite sur les trois caractéristiques suivantes : les changements dans l’état civil, la cohorte d’entrée et l’âge du prestataire. Les équations économétriques incluent des modèles simples de transition ainsi que des modèles de hasard de la probabilité de sortir du régime SRG. Parmi les résultats présentés dans cette étude, il est à noter qu’il y a une incidence non-triviale de délai dans les entrées dans le programme et dans les sorties, conditionnellement à la réception antérieure d’une prestation. Les femmes qui transitent du mariage au célibat sont plus enclines à entrer, alors que c’est le contraire pour les hommes. Les modèles de hasard de la probabilité de sortir du programme SRG, conditionnellement à la durée de la prestation, révèlent un effet négatif de dépendance de la durée. La probabilité d’entrer dans le régime, conditionnellement à n’avoir reçu aucune prestation lorsque l’individu est éligible, diminue avec l’âge.
Keywords: Old age income security; benefit receipt; maritial status; transitions between states; duration effects; 2015E; sécurité de revenu des personnes âgées; prestations; état civil; transitions entre deux états; effets de durée